Submillimeter Array Observations of the RX J1633.9-2442 Transition Disk: Evidence for Multiple Planets in the Making - Cieza, Lucas A. (2012)
Fil: Cieza, Lucas A. University of Hawaii, Manoa, Institute for Astronomy, USA.